2017
DOI: 10.1007/s10295-016-1777-z
|View full text |Cite
|
Sign up to set email alerts
|

Efficient bioconversion of l-glutamate to γ-aminobutyric acid by Lactobacillus brevis resting cells

Abstract: This work investigated the efficient bioconversion process of L-glutamate to GABA by Lactobacillus brevis TCCC 13007 resting cells. The optimal bioconversion system was composed of 50 g/L 48 h cultivated wet resting cells, 0.1 mM pyridoxal phosphate in glutamate-containing 0.6 M citrate buffer (pH 4.5) and performed at 45 °C and 180 rpm. By 10 h bioconversion at the ratio of 80 g/L L-glutamic acid to 240 g/L monosodium glutamate, the final titer of GABA reached 201.18 g/L at the molar bioconversion ratio of 99… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 29 publications
0
34
0
Order By: Relevance
“…However, it was previously reported that GABA can be increased by soaking, germination of the soybean [6,10]. In particular, several microorganisms generally recognized as safe including lactic acid bacteria (LAB) such as Lactobacillus brevis [11][12][13][14][15], Lactobacillus paracasei [16], and Enterococcus raffinosus [17] have been widely studied and applied in GABA production over the last few years. Interestingly, GA is used to produce GABA, which is contained in most soybeans.…”
Section: Introductionmentioning
confidence: 99%
“…However, it was previously reported that GABA can be increased by soaking, germination of the soybean [6,10]. In particular, several microorganisms generally recognized as safe including lactic acid bacteria (LAB) such as Lactobacillus brevis [11][12][13][14][15], Lactobacillus paracasei [16], and Enterococcus raffinosus [17] have been widely studied and applied in GABA production over the last few years. Interestingly, GA is used to produce GABA, which is contained in most soybeans.…”
Section: Introductionmentioning
confidence: 99%
“…The highest reported production titer of GABA was achieved with recombinant E. coli strains producing up to 308.96 g/l of this compound on sugar-based media and with the GABA precursor L-glutamate added in excess (Ke et al, 2016;Xu et al, 2017). Lactobacillus brevis strains have been constructed and reported to display GABA production titers up to 201 g/L for resting cells (Shi et al, 2017). Based on all this, both GABA and cadaverine production titers by recombinant B. methanolicus need to be increased to be industrially competitive.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the condition of pH 6 might be unfavorable to the GadB activity and GABA production. It has been reported that GadB exhibited a higher enzyme activity under relatively acidic conditions and a lower pH could increase the GABA yield (Seo et al, 2013;Zhang R. et al, 2014;Shi et al, 2017). Therefore, we compared the conversion rate from sodium glutamate to GABA of strain F44/GadB1C1 at different pH values.…”
Section: Two-stage Ph-control Fermentation Promoted Gaba Accumulationmentioning
confidence: 99%